CCIs' role in promoting transdisciplinary approaches to sustainability. (28th December 2022) - Innerhofer, Elisa; Kofler, Ingrid; Pechlaner, Harald
The following paper discusses the link between transdisciplinarity and cultural and creative industries (CCIs) and shows how they contribute to sustainable development. Based on a case study on a real-world laboratory, the paper illustrates transdisciplinarity in CCIs and their possible impact on sustainable transformation and development. Cultural and creative actors have the ability to think and act creatively, to break boundaries and to cooperate with people across different cultural and creative sectors. Instead of producing and using disciplinary knowledge in a controlled environment, actors of CCI show transdisciplinary engagement in value creation. Based on a case study analysis, the authors show that transdisciplinarity is a common practice in CCI and that CCI can significantly contribute to sustainable development.